晚清美部會華北教會學校系統的形成 The Formation of Mission School System of the A.B.C.F.M. in North China in Late Ch'ing - 周愚文 Yu-Wen Chou (National Taiwan Normal University, 2020)
晚清中國近代教育西化過程中，教會興辦學校是影響因素之一，本研究以最早派員抵華傳教的美部會為例，探討 1860 年後其以直隸通州傳教站學校為據點，漸發展成華北教育中心，再建立教會學校系統，引入美式教育。本研究屬歷史研究，使用該教會年報、名冊、報刊、書籍及傳記等一手史料。研究發現，該會華北差會 1867 年至通州設立初等學塾，後學校數量日增、分布日廣及程度日高。1889 年通州中學升格為潞河書院，1893 年更建構以各傳教站蒙館、潞河中齋及潞河書院的教會學校系統。庚子事變後，美部會與三個差會共組華北教育聯盟，聯合辦學，潞河書院改為華北協和學院。民國初更邁向併校，1918 年合三校為燕京大學。由通州潞河書院發展之例，可見晚清美國教育如何由教會而引入中國的軌跡。 Protestant mission schools were instrumental in the westernization of education in late Ch'ing China and the subsequent borrowing of educational ideas and practices from American education. This article explored mission schools at Tung-chou Chili, established by American Board of Commissioners for Foreign Missions (A.B.C.F.M.) - the first American protestant mission in China in the early 19th century. First-hand sources, such as annual reports, pamphlets, journals, biographies, and books were reviewed in this article. A mission station was established at Tung-chou in 1867, followed by a boys' school. The number of schools was increasing at the time, and their levels were also being elevated. Tung-chou High School was upgraded to North China College at Tung-chou in 1889. Additionally, an American mission school system was established, comprising day and boarding schools in addition to academies and colleges. After the Boxer incident, the North China Education Union was established by four protestant missions, and North China College was transformed into North China Union College. After its merger with Peking Methodist University and North China Union College for Women, North China College turned into a new university, Yenching University, in 1918. A case study of the development of North China College demonstrated the process of American education being transferred into late Ch'ing China.